Severe congenital neutropenia with leukemic transformation in a pediatric patient. A case report - Lujan-Santos, Renzo (2022)
Background: Severe congenital neutropenia is defined as neutrophil count less than 500 cells/mm3, it is characterized by presenting repeated infections in different organs since the first months of life, in addition to the risk of developing leukemic transformation. Case report: A 7-month-old infant presented with recurrent abscesses since the first month of life, progressive neutropenia in the hemogram, later acute myeloid leukemia was diagnosed by flow cytometry, and finally died of septic shock. Conclusion: Infant with congenital neutropenia developed a leukemic transformation not associated to previous treatment with granulocyte stimulating factor (G-CSF). More studies are expected in the future to determine which other factors besides G-CSF are involved in the leukemic transformation of patients with congenital neutropenia in order to provide better diagnostic and therapeutic alternatives in patients affected by this disease.